English Language Students' Perception on the Impact of Merdeka Belajar-Kampus Merdeka (MBKM) Teaching Assistance Program on Pedagogical Knowledge and Skills at the University of Mataram - Rindiyani Ulfa; Yuni Budi Lestari; Ni Wayan Mira Susanti (Journal of English Education Forum (JEEF), 2026)
This study aims to explore the perceptions of English Education students at Mataram University regarding the impact of the Teaching Assistance Program in the Merdeka Belajar Kampus Merdeka (MBKM) policy initiated by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia on the development of their pedagogical knowledge and skills. This study uses a qualitative descriptive approach involving 25 students as through respondents semi-structured interviews, with data analysis conducted thematically through the stages of data reduction, data presentation, and conclusion drawing. The results show that the majority of students have a positive perception of this program, especially in improving their understanding of learning theory, learning strategies, and planning, assessment, and the ability to integrate theory with real practice in the classroom. This program also contributes significantly to the development of pedagogical skills such as classroom management, material delivery, the use of technology-based learning media, communication, and the ability to adapt to student characteristics and the school environment.